Case Report: Tocilizumab for Acute Kidney Graft Dysfunction in Patient Affected by COVID-19 - Barbara, Infante; Silvia, Mercuri; Dario, Troise; Giuseppe, Castellano; Stallone, Giovanni (Frontiers in Medicine, 2021)
The Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was isolated in January 2020 and, on March, the WHO declared the status of a pandemic. It causes a cytokine release syndrome, called "Cytokine storm" characterized by systemic inflammation involving elevated levels of cytokines and hyper-activation of immune-cell; as consequence, this profound alteration in immune system led to an overshooting inflammatory response contributing to morbidity and mortality. Solid organ transplant recipients are at particularly higher risk of developing critical Coronavirus disease 2019 (Covid-19) due to chronic immunosuppression; in fact, establishing the balance between infection and rejection in any transplant recipient is the principal aim when prescribing immunosuppression. These observations, therefore, induced a deep reflection about the management of immunosuppression that is a priority in severe disease manifestations SARS-CoV-2 correlated. Tocilizumab, a humanized monoclonal antibody against IL-6 receptor widely adopted in adult rheumatoid arthritis, is used as rescue therapy for chronic antibody-mediated rejection in kidney transplantation. Data about the use of Tocilizumab as an immunosuppressive drug for treating acute kidney graft dysfunction in a setting of kidney transplanted patients affect by COVID-19 are lacking. Here, we discuss the case of kidney transplant recipient with proven SARS-CoV-2 infection that develops an acute graft dysfunction and the management of immunosuppression with concomitant Tocilizumab administration.